Knowledge and practice of pain management among nurses in labour wards in Ibadan, Nigeria (2016)
Background: It is not clear whether awareness of pain management has influenced the management of labour pain by nurse/midwives in Ibadan, Nigeria. Many women in labour do not get optimal pain relief, despite awareness of the importance of pain management. Aims: This study aimed to assess knowledge and practice of labour pain management among nurse/midwives in Ibadan. Methods: This cross-sectional study included 87 nurse/ midwives on duty in labour rooms of three hospitals in Ibadan, Nigeria. Data were collected using semi-structured questionnaires. Descriptive statistics, Pearson’s and Kendall’s correlation coefficients were used for data analysis. All analyses were performed using IBM SPSS version 20.0 at 5% level of significance. Findings: Two thirds of respondents (66.7%) had a moderate level of knowledge, and 34.5% managed labour pain through back massage/psychotherapy. Knowledge of pain management was associated with level of education (τ =0.82; P (τ =0.82; P<0.001) while good practice of pain management was associated with good knowledge (r =0.49; P<0.001). The association between good practice and years of working experience just failed to be statistically significant (P=0.06). Conclusions: Nurse/midwives in Ibadan have moderate knowledge of labour pain management. Participants in this study primarily used back massage and psychotherapy. There is need for improvement in knowledge of labour pain management through continuing education for nurse/midwives in Ibadan.